Cash Transfers, Labor Supply, and Gender Inequality: Evidence from South Africa. Issue 4 (2nd October 2019) - Scarlato, Margherita; d'Agostino, Giorgio
ABSTRACT: This paper provides an empirical analysis of the impact of the Child Support Grant (CSG) implemented in South Africa on the labor supply of the parents of beneficiary children. The aim is to assess whether the program improved or lessened gender inequality in the labor market. Using data from a national panel survey and applying a fuzzy regression discontinuity design that exploits an expansion in eligibility due to a discontinuous change in age eligibility, the results show that the CSG had a negative effect on the probability of parents of beneficiary children being employed and mixed effects on the participation in the labor force, with substantial heterogeneity by gender and by other individual and household characteristics. Overall, the evaluation suggests that the program provided support to members of vulnerable households in coping with the constraints of the South African labor market, but it did not reshape existing gender inequalities.